LA SEGURIDAD Y PREVENCIÓN DE RIESGOS EN EL DESEMPEÑO LABORAL DE LOS TRABAJADORES DE LA EMPRESA ELÉCTRICA REGIONAL DEL SUR S.A. Y EL ROL DEL TRABAJADOR SOCIAL. - Masache Chalaco, Elvis Darwin (2015)
Job insecurity and the prevention of occupational risks is a social problem, which is associated with several factors such as declining health and increased risk of excessive work to which they are exposed daily workers in the electric company, so that the present research work entitled "Insecurity and Risk Prevention in the job performance of Workers of the South Regional Electricity Company SA (EERSSA) and the Role of Social Worker ", was developed through a process of analysis to workers of the Regional Electric Company South of the City of Loja, where it had as its central objective Improve Work Safety Workers the South Regional Electricity Company SA In this research an intervention model supported by Community Self methodology is proposed, which is based on three stages as are: Stage One: Initial exchange with the subject plaintiff or in need of professional action. Stage: Exploring the stage and Third Stage: Process diagnosis and search for a solution, without neglecting the document review of each of the indicators studied. The sample volume was 30 workers, their approach was quantitative and qualitative; The findings were obtained from the data obtained from the surveys revealed that workers have suffered accidents electrocution, electrical burns, the company does not employ adequate safety measures, implementation materials and tools necessary safety talks ongoing training and risk prevention.